IEEE MTT-S International Microwave Symposium Digest, 2005. 2005
DOI: 10.1109/mwsym.2005.1516663
|View full text |Cite
|
Sign up to set email alerts
|

Wideband reflective array based on loaded metal rings

Abstract: Wideband spiraphase-type reflective arrays based on loaded metal rings are analyzed. It is demonstrated that these arrays can redirect an incident circularly polarized wave in the directions determined by elevation angles up to 40° in a 2:1 frequency band with conversion loss less than 1 dB. A full-wave mathematical model has been developed to predict the characteristics of these arrays. This mathematical model was used for the synthesis of two arrays for X-Ku and K-Ka bands. Minimotor-driven elements have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many microstrip elements of this type have been presented in the literature [2], [3], [4]. These reflectarrays have all been static, but in [5] it was suggested that a micromotor could be placed below each element to create a phased reflectarray.…”
Section: Introductionmentioning
confidence: 99%
“…Many microstrip elements of this type have been presented in the literature [2], [3], [4]. These reflectarrays have all been static, but in [5] it was suggested that a micromotor could be placed below each element to create a phased reflectarray.…”
Section: Introductionmentioning
confidence: 99%